Correntes do pensamento geográfico e condições de trabalho: ensinar geografia na rede municipal de Santa Maria/RS - Leal, Carmen Luyara Canabarro (2016)
This dissertation brings a research on geography education in the Municipal Network of Santa Maria/RS, mediation between the trends of geographical thought and working conditions that afflicts education professionals. It is considered the various currents of geographical thought that have arisen lately and come to the schools, according to the training and design of each teacher and the work context to which they belong. Thus, it has been as problematic trace some parameters for understanding the following question: how is to teach geography in schools in Santa Maria/RS? To understand this question outlined aspects of transformation in the teaching of geography in recent years to realize the manifestation of geographical thought currents and the working situation of the professional in the midst of capitalist logic. In order to achieve the goals held interviews with fifteen Geography teachers from municipal public of Santa Maria/RS, with issues relating to the two axes raised. It found a lack of adequate continuing education, dealing with issues deemed appropriate by the teachers themselves; the need for better working conditions, especially as regards the best infrastructure and more professionals, considering that the current overloaded. Finally, he noted that the teacher's role is in addition to teaching a critical Geography, is in direct dealing the social nature of issues and the structure of the current economic system, which precarious education of the mass of workers and precarious their conditions work.